The teachers’ perception: The use of Wayground in EFL learning - Alfian Khabibi; Priyatmojo, Arif Suryo (Universitas Negeri Semarang, 2025)
This chapter examines the role of Wayground (formerly Quizizz) in improving English as Foreign Language (EFL) skills through a case study perspective examining teachers’ perceptions. The aim is to discuss teachers’ positive and negative perceptions regarding the advantages, challenges, and practical steps for optimization in an EFL context. The focus of the discussion is derived from qualitative insights gained from previous research paired with empirical research highlighting key issues such as lack of student engagement, rote data-based assessment without learning, and test anxiety. Teachers largely have a positive view of Wayground due to its interactive features and real-time feedback mechanisms that actively engage and motivate learners. However, challenges related to quiz design, technological infrastructure, and the need for ongoing professional development are also important to further explore. This chapter outlines teachers’ perceptions of Wayground, its challenges, and specific educator-centered strategies aimed at increasing participatory engagement while addressing data-related instructional and technological barriers all framed in maximizing the benefits offered by Wayground. Ultimately, this chapter contributes to the understanding of how powerful technological tools like Wayground can revolutionize EFL pedagogy towards a more engaging, effective, and inclusive educational paradigm.